2021
DOI: 10.2139/ssrn.3950094
|View full text |Cite
|
Sign up to set email alerts
|

Promise Not Fulfilled: Fintech Data Privacy, and the GDPR

Abstract: This article analyzes how the General Data Protection Regulation (GDPR) has affected the privacy practices of FinTech firms. We study the content of 308 privacy statements respectively before and after the GDPR became binding. Using textual analysis methods, we find that the readability of the privacy statements has decreased. The texts of privacy statements have become longer and use more standardized language, resulting in worse user comprehension. This calls into question whether the GDPR has achieved its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…However, Degeling et al (2019) found that while most websites adjusted their privacy policies and implemented consent mechanisms in the months immediately following GDPR enforcement, some did not comply and did not provide users with means to meaningfully consent to tracking. Dorfleitner et al (2021) found that the readability of privacy policies for German financial technology firms decreased after the GDPR, while their length and the quantity of data processed increased. Sanchez-Rola et al (2019) found that, despite the presence of the opt-out mechanism, it was still difficult for users to avoid being tracked.…”
Section: Prior Literaturementioning
confidence: 99%
“…However, Degeling et al (2019) found that while most websites adjusted their privacy policies and implemented consent mechanisms in the months immediately following GDPR enforcement, some did not comply and did not provide users with means to meaningfully consent to tracking. Dorfleitner et al (2021) found that the readability of privacy policies for German financial technology firms decreased after the GDPR, while their length and the quantity of data processed increased. Sanchez-Rola et al (2019) found that, despite the presence of the opt-out mechanism, it was still difficult for users to avoid being tracked.…”
Section: Prior Literaturementioning
confidence: 99%
“…The security and safety of a person and his or her data is very much at risk. Though there are laws like General Data Protection Regulation [GDPR] which was created to deal with these kinds of risks however, these laws are governing an entity communicating with Europe (Dorfleitner et al, 2021). Though India is bringing in Digital Personal Data Protection Bill, 2022, however, it is not passed in the Parliament yet.…”
Section: Contemporary Cyber Threats In India To Fin-tech Technologymentioning
confidence: 99%
“…In the context of cybersecurity, the literature emphasizes the importance of data security, customer trust, and user design interface in influencing the adoption of Fintech (Stewart & Jürjens, 2018). Additionally, the theoretical construct for future Fintech industry development should ensure sound security mechanisms based on observed security and privacy concerns and their solutions (Dorfleitner et al, 2021). Moreover, the effects of trust, security, and privacy are crucial in understanding the pattern of adoption, indicating the significance of these factors in shaping user behavior (Shin, 2010).…”
Section: Behavioral Analysis In Fintech Cybersecuritymentioning
confidence: 99%